Impact Of Micro And Macro Dynamics On Share Price Of Non-Financial Listed Firms In Textile Sector Of Pakistan - Raza, Hamad; Gillani, Syed Muhammad Ahmad Hassan; Ahmad, Humara; Qureshi, Muhammad Imran; Khan, Nohman (The journal of contemporary issues in business and government, 2021)
Share price determination have always been of interest in the financial world and capital market as investors give critical importance in understanding why prices move up and down. In this regard, multiple researches have been conducted in literature, which provides mixed opinion and findings related to determinants of share price in terms of positive or negative influence as determinants differs among various countries. The current study aims to investigates the impact of micro and macro dynamics on share price, particularly non-financial firms listed in textile sector on Pakistan Stock Exchange (PSX). The study collected data of 62 listed textile firms by using secondary sources such as DataStream, annual reports, SBP and (PSX). This study used panel data analysis to analyse the impact on share price. from period 2009 to 2017. Different statistical analysis methods such as descriptive statistics, correlation matrix, pooled OLS, Breusch and Pagan LM test, Hausman test and fixed effect model is employed to perform analysis. The findings suggest that micro dynamics (EPS, BVS and LNFS) and macro dynamics (GDP) are positively and significantly related to share price of firm in textile sector of Pakistan. However, micro dynamics (DPS) and macro dynamics (INF) are found to be insignificant. The current study adds to the existing body of literature and ongoing debate on the determinants that influence the share price in developing market, particularly textile sector of Pakistan.